Alternasi Bunyi Bahasa Indonesia dalam Kognat Melayu Ulu Kapuas - Fauzi Syamsuar (Aksara, 2023)
Indonesian is derived from Standard Malay; while Ulu Kapuas is a dialect of Malay. Sameness between the two language codes is shown by their identical cognates. There are other cognates showing sound alternations. This article describes the sameness and the sound alternations undergone by the cognates. The alternations involve segments (consonants, vowels, diphthongs, and soundclusters) and show morphophonemic alternations involving replacement, addition, deletion, and syllabic position replacement of segments; the alternations also involve one of the suprasegmental features, i.e., length. The data corpora are in forms of the phonological forms of the cognates. The phonological forms of Ulu Kapuas cognates are obtained from and/or based on previous studies on phonological aspects of Ulu Kapuas lexical items conducted by Yusriadi (2007). Meanwhile, Indonesian cognates are Indonesian lexical items available in Kamus Besar Bahasa Indonesia becoming the equivalents for Ulu Kapuas lexical items afore-mentioned; and their phonological forms are determined by referring to the rules of graphemephoneme correspondences in Indonesian proposed by Fauzi (2015). Consonant weakening, consonant strengthening, lenition, fortition, vowel laxing, vowel tensing, diphthongization, monophthongization, tongueposition change in vowel production, metatheses, sound deletion, haplology, sound addition, assimilation, dissimilation, glottalization, nasalization, sound lengthening, word shortening, word lengthening, and dereduplication become findings. Phonotactics and the distributions of segments in the cognates shared by the two language codes also become findings.AbstrakBahasa Indonesia terderivasi dari bahasa Melayu Baku; dan Ulu Kapuas merupakan salah satu dialek bahasa Melayu. Kesamaan di antara dua kode bahasa itu ditunjukkan oleh kognat identik yang dimiliki bersama. Terdapat kognat lain yang menunjukkan alternasi bunyi. Artikel ini mendeskripsikan kesamaan dan alternasi bunyi yang dialami oleh kognat tersebut. Alternasi bunyi melibatkan segmen (konsonan, vokal, diftong, dan untaian bunyi) serta menunjukkan sejumlah alternasi morfofonemik yang melibatkan penggantian, penambahan, penghilangan, dan perubahan posisi silabis segmen; alternasi morfofonemik itu juga melibatkan perpanjangan bunyi sebagai salah satu aspek prosodi. Korpus data berupa bentuk fonologis kognat. Bentuk fonologis kognat Ulu Kapuas diperoleh dari dan/atau didasarkan pada kajian terdahulu atas aspek fonologis satuan leksikal Ulu Kapuas yang dilakukan oleh Yusriadi (2007). Sementara itu, kognat Indonesia merupakan satuan leksikal Indonesia yang ada dalam Kamus Besar Bahasa Indonesia (KBBI) dan merupakan padanan bagi satuan leksikal Ulu Kapuas tersebut di atas; dan bentuk fonologisnya ditentukan dengan merujuk ke kaidah grafem-fonem dalam bahasa Indonesia yang dianjurkan oleh Fauzi (2015). Pelemahan konsonan, penguatan konsonan, lenisi, fortisi, pengenduran vokal, penegangan vokal, diftongisasi, monoftongisasi, perubahan posisi-lidah dalam produksi vokal, penggabungan bunyi, metatesis, penghilangan bunyi, haplologi, penambahan bunyi, asimilasi, disimilasi, glotalisasi, nasalisasi, perpanjangan bunyi, pemendekan kata, pemanjangan kata, dan de-reduplikasi kata menjadi temuan. Kaidah fonotaktis serta persebaran segmen dalam kognat yang dimiliki oleh dua kode bahasa itu pun menjadi temuan.